Effect of Ni–P thickness on solid-state interfacial reactions between Sn–3.5Ag solder and electroless Ni–P metallization on Cu substrate - Kumar, Aditya (2013)
Solid-state interfacial reactions between Sn–3.5Ag solder and electroless Ni–P metallization on Cu substrate were investigated for three different Ni–P thicknesses. It was found that during interfacial reactions, Ni3Sn4 intermetallic grows at the Sn–3.5Ag/Ni–P interface along with the crystallization of electroless Ni–P layer into Ni3P compound. Additional interfacial compounds (IFCs) such as Ni–Sn–P, Cu3Sn, Cu6Sn5, (Ni1−xCux)3Sn4, and (Ni1−xCux)6Sn5 were also found to grow at the Sn–3.5Ag/Ni–P/Cu interfaces depending upon the Ni–P thickness. In the sample with thin Ni–P layer, formation of these IFCs appeared at lower aging temperature and within shorter aging duration than in the samples with thicker Ni–P. The complete dissolution of electroless Ni–P layer into Ni3P and Ni–Sn–P layers was found to be the main cause for the growth of additional IFCs. Across the Ni3P and Ni–Sn–P layers, diffusion of Cu and Sn takes place resulting in the formation of Cu–Sn and Ni–Cu–Sn intermetallics. It is shown in this paper that multi-layered IFC growth at the Sn–3.5Ag/Ni–P/Cu interfaces can be avoided by the selection of proper Ni–P thickness.